SUNFLOWER OIL PRICING FACTORS (Development Service Industry Management, 2024)
The article presents approaches to the classification of pricing factors for agricultural products and their processing products, based on which the peculiarities of their manifestation in the price of sunflower oil are characterized. The presence of various variants of the generalization of pricing factors testifies to the importance of this scientific and practical problem. The price is a market indicator that determines the efficiency of the sunflower oil producer's activities, therefore, in order to make management decisions, an understanding of the entire set of pricing conditions in the market is required. Considering this, it was established that there are external and internal factors affecting the price of sunflower oil. External factors are proposed to include: ratio of supply and demand on the oil market; state of competition in the industry; development of new technologies; level of economic growth; financial and economic measures of state stimulation of the economy; weather and climatic conditions; transitional reserves of vegetable oil residues in the world; seasonality of production; instruments of trade policy regulation have been introduced; prices for other types of oils; consumer attitudes of the population. Among the internal factors, it is suggested to understand: the level of oil production costs; the desired amount of profit; indicators of the size and geographical location of the enterprise; approaches to the use of elements of the marketing complex; coverage of distribution channels.The conditions for a decrease or increase in the price of oil with various variants of the manifestation of the above factors have been determined. The price of sunflower oil is under the constant influence of a whole set of factors, the combination of which forms the rules of market functioning and is quite often accompanied by unpredictable consequences. The given list of factors should be taken into account by participants in market relations when forecasting trends in the price of sunflower oil in order to eliminate the risks of obtaining negative indicators in economic activity.
Keywords: sunflower oil; price; pricing factors; market; agricultural products; enterprise; business